Biological and physical controls on the flux and characteristics of sinking particles on the Northwest Atlantic margin - Hwang, Jeomshik; Manganini, Steven J.; Park, Jonglin; Montlucon, Daniel B.; Toole, John M.; Eglinton, Timothy I. (Journal of Geophysical Research: Oceans, 2017)
Author Posting. © American Geophysical Union, 2017. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research: Oceans 122 (2017): 4539–4553, doi:10.1002/2016JC012549. Biogenic matter characteristics and radiocarbon contents of organic carbon (OC) were examined on sinking particle samples intercepted at three nominal depths of 1000 m, 2000 m, and 3000 m (∼50 m above the seafloor) during a 3 year sediment trap program on the New England slope in the Northwest Atlantic. We have sought to characterize the sources of sinking particles in the context of vertical export of biogenic particles from the overlying water column and lateral supply of resuspended sediment particles from adjacent margin sediments. High aluminum (Al) abundances and low OC radiocarbon contents indicated contributions from resuspended sediment which was greatest at 3000 m but also significant at shallower depths. The benthic source (i.e., laterally supplied resuspended sediment) of opal appears negligible based on the absence of a correlation with Al fluxes. In comparison, CaCO3 fluxes at 3000 m showed a positive correlation with Al fluxes. Benthic sources accounted for 42 ∼ 63% of the sinking particle flux based on radiocarbon mass balance and the relationship between Al flux and CaCO3 flux. Episodic pulses of Al at 3000 m were significantly correlated with the near-bottom current at a nearby hydrographic mooring site, implying the importance of current variability in lateral particle transport. However, Al fluxes at 1000 m and 2000 m were coherent but differed from those at 3000 m, implying more than one mode of lateral supply of particles in the water column. NSF Ocean Sciences Chemical Oceanography program Grant Numbers: OCE-0425677, OCE-0851350; Ocean and Climate Change Institute of WHOI 2017-12-01